New theoretical solution for soft soil consolidation under vacuum pressure via horizontal drainage enhanced geotextile sheets - Chen, Hao (2024)
Land reclamation is a major construction activity in Singapore and other Asian countries. When granular fills become scarce, soft materials have to be used for land reclamation. A new land reclamation and soil improvement method using vacuum preloading and horizontal drainage enhanced non-woven geotextile (HDeG) sheets for soft soil consolidation has been proposed to reduce consolidation time and save costs. This paper presents a new theoretical solution for analysing the consolidation process of soil under vacuum pressure via horizontal drainage enhanced geotextile sheets as such a solution is not available yet. To verify the proposed theoretical solution, model tests and finite element analyses (FEA) have also been conducted. The proposed analytical solution agrees well with the results from FEA and the model tests in settlement, average effective stress and degree of consolidation. Thus, this solution could be used for design and analysis for land reclamation with soft materials consolidated using vacuum preloading together with HDeG sheets or other horizontal drainage materials with an adequately high transmissivity. The prediction of the consolidation performance relies on the proper selection of the coefficient of consolidation based on the effective stress history of soil.